Spectral Signage - Steven Feld; Meghanne Barker; Constantine V. Nakassis (Semiotic Review)
This discussion with Steven Feld occurred online on May 4, 2020 for around two-and-a-half hours. It covers a wide range of topics: Feld’s training and background; the relations of linguistic anthropology, semiotics, linguistics, film studies, visual anthropology, musicology, and acoustemology; linguistic poetics, iconic power, and visual form; spectralism and the trace; relationality and interspeciality; the Anthropocene, the atomic bomb, and COVID-19; among other topics. This conversation builds upon Feld’s keynote lecture, “Spectral Signage” for the workshop Sense and Semiosis: Bridging Conversations between Linguistic and Visual Anthropology (September 26–28, 2019, at the University of Chicago, organized by Constantine V. Nakassis and Meghanne Barker, funded by the Wenner-Gren Foundation), as well as the discussion that followed. A recording of the online conversation was transcribed by Emily Kuret and Constantine V. Nakassis, and edited by Meghanne Barker, Constantine V. Nakassis, and Steven Feld for readability, completeness, and context. References were later added as endnotes, and visual images and sound recordings discussed during the conversation were intercalated into the final text.